Functional characterisation of a nicotinic acetylcholine receptor α subunit from the brown dog tick, Rhipicephalus sanguineus() - Lees, Kristin (Elsevier Science, 2014)
Ticks and tick-borne diseases have a major impact on human and animal health worldwide. Current control strategies rely heavily on the use of chemical acaricides, most of which target the CNS and with increasing resistance, new drugs are urgently needed. Nicotinic acetylcholine receptors (nAChRs) are targets of highly successful insecticides. We isolated a full-length nAChR α subunit from a normalised cDNA library from the synganglion (brain) of the brown dog tick, Rhipicephalus sanguineus. Phylogenetic analysis has shown this R. sanguineus nAChR to be most similar to the insect α1 nAChR group and has been named Rsanα1. Rsanα1 is distributed in multiple tick tissues and is present across all life-stages. When expressed in Xenopus laevis oocytes Rsanα1 failed to function as a homomer, with and without the addition of either Caenorhabditis elegans resistance-to-cholinesterase (RIC)-3 or X. laevis RIC-3. When co-expressed with chicken β2 nAChR, Rsanα1 evoked concentration-dependent, inward currents in response to acetylcholine (ACh) and showed sensitivity to nicotine (100 μM) and choline (100 μM). Rsanα1/β2 was insensitive to both imidacloprid (100 μM) and spinosad (100 μM). The unreliable expression of Rsanα1 in vitro suggests that additional subunits or chaperone proteins may be required for more robust expression. This study enhances our understanding of nAChRs in arachnids and may provide a basis for further studies on the interaction of compounds with the tick nAChR as part of a discovery process for novel acaricides.